Tripterygium glycosides sensitizes cisplatin chemotherapeutic potency by modulating gut microbiota in epithelial ovarian cancer - Zhan, Xinlu; Zuo, Qi; Huang, Genhua; Qi, Zhanghua; Wang, Yufan; Zhu, Sihong; Zhong, Yanying; Xiong, Yifei; Chen, Tingtao; Tan, Buzhen (Frontiers in Cellular and Infection Microbiology, 2023)
Epithelial ovarian cancer (EOC) is a fatal gynecological malignancy with limited therapeutic options. Previous research has demonstrated that Tripterygium glycosides (GTW) can enhance effectiveness of cisplatin (DDP) chemotherapy against EOC. However, the underlying mechanism of GTW alleviating EOC still remains unclear. In this article, an ID8 cell-derived xenograft mouse model was established to evaluate the anti-tumor efficacy of GTW combined with DDP. Consistent with previous findings, the results suggested that GTW combined with DDP can exhibit a stronger tumor suppressive effect than DDP alone. Additionally, GTW was found can further exert gastrointestinal protection against DDP by reducing pathological damage on colon tissue. Secondly, to verify whether gut microbiota play an instrumental role in GTW's anticancer effect, we treated mice models with antibiotic to eliminate gut microbiota. And our experimental results indicated that all drug groups showed a weaker tumor suppressive effect and more severe gastrointestinal damage post antibiotic supplement. At genus level, the relative abundance of Lactobacillus was dramatically diminished by the antibiotic treatment, while combined treatment of GTW and DDP can significantly restore the level. Moreover, we performed Lactobacillus acidophilus transplantation and healthy mice fecal microbiota transplantation experiments to further investigate the link between the anticancer effect of GTW and gut microbiota. Our results suggested that both cisplatin-sensitizing and intestinal barrier-protecting effects of GTW can be recovered to a different extent. In conclusion, our results indicated that GTW is a promising chemosensitization and intestinal barrier repair drug for EOC, and the potential mechanism may corelate with the restoration of the compromised intestinal microbial balance.